AUTOMATIC CRACK DETECTION - Anuja Kade; Shweta Shete; Mrunal Kulkarni; Anagha Kunte (International Journal of Innovations in Engineering Research and Technology, 2021)
The issue of detection is very criticalin all the manufacturing companies. Therefore we intend to aid in defect detection by bringing in an automatic crack detection using digital image processing.When vision inspection of a product is done manually, there are chances of human error taking place or lack of efficiency or irresponsibility in some cases. This may bring a faulty piece in application leading to the possibility of failure of that component. In order to avoid such a risk, we are trying to develop anautomatic crack detection system